Didactic dissonance—embracing the tension between classroom and clinical education - Mardian, Aram S.; Villarroel, Lisa; Kemper, Lori; Quist, Heidi E.; Hanson, Eric R. (Frontiers in Medicine, 2023)
The US is undergoing a transformation in the way pain is viewed and treated. This transformation affects pain education, as some degree of disconnect will be expected between what is taught in classroom settings and what learners observe in clinical settings. We term this disconnect “didactic dissonance” and propose a novel process to harness it as a learning tool to further pain education. Based on principles of transformative learning theory, we describe a structured, three-step process beginning with 1) priming learners to recognize didactic dissonance and identify specific examples from their education, followed by 2) encouraging learners to search the primary literature to resolve observed dissonance and reflect on the system factors that created and perpetuated the disconnect, and then 3) providing an opportunity for learner reflection and planning for how they will address similar situations in future practice and teaching environments. Fostering an environment conducive to learning - through modeling the intellectual virtues of curiosity, humility, and creativity - is a critical task for educators when implementing this process. Recognizing challenges faced by educators in both classroom and clinical settings, it may be a more feasible first step to integrate the concept of didactic dissonance intoexisting curricular elements. For programs able to implement the full three-step process, a discussion guide along with an example of a facilitated discussion have been provided. While proposed in the context of pain education, this transformational approach can be utilized across all topics in medical education to foster autonomous lifelong learning.